1986
DOI: 10.1002/pen.760260207
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behavior of a single screw plasticating extruder part II: Dynamic modeling

Abstract: The dynamic response of a 2.5 inch plasticating extruder and the extrusion line are modeled using high density polyethylene and acrylics us extrudate. Screw speed, back pressure valve position, and material changes are used as forcing functions. Three fundamental transfer functions in the Laplace domain: a first order, a second order, and a lead‐lag, are developed to simulate the short term and long term responses of temperatures, pressures, and extrudate thickness. A kinetic‐elastic model which can predict rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…They are also promising tools for product development and quality improvement. Dynamic analysis of extrusion data has been widely reported in the plastics extrusion literature (4,(7)(8)(9) and the same basic principles of polymer extrusion can be applied to food extrusion. However, the nature of the food ingredients, interaction between the food components, and physicochemical changes such as protein denaturation and starch gelatinization make modeling of food extrusion more complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are also promising tools for product development and quality improvement. Dynamic analysis of extrusion data has been widely reported in the plastics extrusion literature (4,(7)(8)(9) and the same basic principles of polymer extrusion can be applied to food extrusion. However, the nature of the food ingredients, interaction between the food components, and physicochemical changes such as protein denaturation and starch gelatinization make modeling of food extrusion more complex.…”
Section: Introductionmentioning
confidence: 99%
“…For the various fluctuations which occur in an extrusion process, steady state models cannot predict the response of the system and the influence of the fluctuations on the extruder performance. Therefore, a dynamic extrusion model is essential for the design of a control system for extrusion (4). Dynamic empirical models offer an understanding of the extrusion process during the transition periods (period between two separate steady states).…”
Section: Introductionmentioning
confidence: 99%
“…Costin et al 22 critically reviewed dynamic modeling and control of plasticating extruders, and concluded that the gross dynamic input/output behavior may be generally described by simple first-/second-order models. Chan et al 23 studied the pressure responses to screw speed changes as a first-order function times a lead-lag function to effectively model responses with an initial increase or decrease, followed by an exponential decay to the final steady state value. Equation (5a) represents a firstorder process with a dead time in the time domain, while eq.…”
Section: Table IV Steady State Process Gains For Step-input Variationmentioning
confidence: 99%
“…Chan and Lee [23], Chan et al [24] and Nelson et al [25] proposed Laplace transfer function models (e.g., a first order, a second order and a lead-lag) to describe dynamic responses of an extrusion process. Laplace transfer function models accounted for the basic type of temperature and pressure responses with fitting of a phenomenological kinetic-elastic model to calculate other required parameters.…”
Section: A Control Schemes Based On Laplace Transform or Time Seriesmentioning
confidence: 99%